Investigation on the wear behaviour of Aluminium alloys at cryogenic temperature and subjected to cryo -treatment. (April 2019) - Padmini, B V; Sampathkumaran, P; Seetharamu, S; Naveen, G J; Niranjan, H B
Abstract: The published information on ferrous and nonferrous metals especially Aluminium alloys subjected to deep cryogenic treatment (DCT) have yielded much improved mechanical, tribological and thermal properties resulting in improved properties in the field. Keeping the above aspects in view, tribological studies have been taken up in this work with the main objective of evaluating the wear resistance of the most used Aluminium alloys viz: Al 2024, 6082 and 7075 samples at cryogenic temperature and subjected them to deep cryogenic treatment for 64 hrs. The novelty of the work lies in conducting the wear test in cryogenic atmosphere which is the first of its kind as meagre report is available. It is observed from the wear data that the slide wear resistance and coefficient of friction evaluated in the laboratory conditions show superior wear resistance for the load application of 40N and 50N and lower friction levels for the samples subjected to sliding at cryogenic temperature as well as for the samples deeply cryo treated compared to the untreated ones. The data have been substantiated by Scanning Electron Microscopic features (SEM).